Using iPads/Tablets as a teaching tool: Strategies for an electrical engineering classroom - Ravishankar, J.; Epps, J.; Ladouceur, F.; Eaton, R.; Ambikairajah, E. (2014 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE), 2014)
This paper explores the potential impact of the iPad/Tablet and its applications on teaching and learning, especially in the area of electrical engineering. The authors discuss the effective and innovative strategies introduced by the School of Electrical Engineering and Telecommunications, the University of New South Wales (UNSW). The unique apps developed for Electrical Engineering are elaborated. The on-going survey results that examine the iPad as a pedagogical tool are described along with the implications for further implementation. The results suggest that these devices may offer an exciting platform for creating content in a collaborative, interactive way.